Tribocorrosion-Resistant Surface for TiO2 as a Function of Load and Sliding Speed (2023)
The applications projected in the coatings are in implants with the lower extremities since they require a great load capacity and are essential for walking. Therefore, the use of devices or implants is necessary for recovery, osteosynthesis, and fixation. The tribocorrosive behavior of nanostructured compounds based on titanium oxide with an intermediate layer of gold deposited on titanium substrates was determined. These coatings were obtained using the reactive magnetron sputtering technique. Tribocorrosive properties were evaluated at sliding speeds of 3500 mm/min, 4500 mm/min, 6000 mm/min, 7500 mm/min, and 9000 mm/min with loads of 1 N, 2 N, 3 N, 4 N, and 5 N. The coatings were characterized by X-ray photoemission spectroscopy and X-ray diffraction, and the surface roughness was analyzed by atomic force microscopy. The dual mechanical and electrochemical wear tests were carried out with a potentiostat coupled to a pin on the disk system. The system was in contact with a hanks solution (37 ◦C), which acted as a lubricant. Structural characterization made it possible to identify the TiO2 compound. In the morphological characterization, it was found that the substrate influenced the surface properties of the coatings. The tribological behavior estimated by the wear rates showed less wear at higher load and sliding speeds. It was shown that it is possible to obtain coatings with better electrochemical and tribological performance by controlling the applied load and slip speed variables. In this study, a significant decrease corresponding to 64% was obtained, specifically in the speed of deterioration, and especially for a load of 5 N, depending on the sliding speed that went from 0.2831 mpy (Mils penetration per year) to 3500 mm/min compared to 0.1045 mpy at 9000 mm/min, which is explained by the mechanical blockage induced by the coating.